The Nature of Self-Directed Learning and Transformational Learning in Self-Managing Bipolar Disorder to Stay Well - Wendy A. Francik (Adult Education Research Conference, 2013)
Experiences in learning to stay well with bipolar disorder were explored. Participants’ descriptions illustrated how self-directed learning and transformational learning transpired in self-management. Acceptance and making meaning of bipolar disorder prompted learning autonomy. Adult learning experiences, learning resources, taking ownership, and taking action facilitated the dynamics of learning.